Factors influencing local people's participation in watershed management programs in Iran - Bagherian, Reza; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Ahmad, Shamsuddin (IDOSI Publications, 2009)
The degree of popular participation in development programs is a major determinant of success or failure, but the factors which make participation efforts successful still remained a mystery. This study was designed to discover this mystery and determine the factors that influence local people’s participation in Watershed Management Programs by using the social exchange framework. The data for this study were gathered from 200 respondents through personal interview during August and September 2008. The findings of this study showed that level of participation in WMP was moderate; however people preferred more involvement in social rather than economical and environmental activities. Correlation analysis indicated that six factors: 1) satisfaction of prior programs, 2) attitude toward WMP, 3) knowledge of WMP, 4) alternative monthly income, 5) total monthly income and 6) Met expectations of WMP have positive and significant relationship with level of people’s participation in WMP. However, regression analysis discovered that among these factors, five factors provided the best prediction for the level of people’s participation in WMP and explained 45 % of the variation. These five factors were; level of people’s satisfaction of prior programs, people’s attitude toward WMP, people’s knowledge of WMP, their monthly income from alternative occupation and their expectations of WMP. The result of this study also provided a number of theoretical and practical implications and recommendations to increase the level of participation in WMP.